Design of bio-based organic phase change materials containing a "safety valve". Issue 21 (15th October 2021) - Wuliu, Yishun; Liu, Jingkai; Zhang, Liyue; Wang, Shuaipeng; Liu, Yuejun; Feng, Jianxiang; Liu, Xiaoqing
Abstract : The concept and function of oxazine ring's "safety valve" for safer PCMs have been proposed and verified. Abstract : Energy efficiency and resource utilization are considered to be necessary for sustainable development. Organic phase change materials (PCMs) as an effective thermal energy storage tool have attracted great interest, but non-renewable ingredients, low stability and their unsafe nature largely restrict their sustainability. Herein, a series of bio-based benzoxazine-derived PCMs were developed, in which green preparation, efficient energy conversion, and safe utilization can be simultaneously achieved. Through the Mannich condensation reaction, novel PCMs can be easily synthesized with good yield and high atom economy by combining natural 3-pentadecylphenol (a cardanol derivative) and amine sources. The resulting PCMs exhibited adjustable latent heat (48.78–147.02 J g −1 ) by altering raw materials, which are close to their commercial unsustainable counterparts. As an example, C-aa-12 also showed considerable recycling ability after 100 times repeated use. In addition, due to the designed structure, as-prepared PCMs also possessed more excellent properties of thermal stability ( T d50% was increased by 65.1%) and flame retardancy (HRR was reduced by 39.4%) compared with traditional ones, making them promising in a wider application field.